Development of isomer-free fullerene bisadducts for efficient polymer solar cells. Issue 6 (12th May 2016) - Xiao, Zuo; Geng, Xinjian; He, Dan; Jia, Xue; Ding, Liming
Abstract : A prebisaddition-confined bisfunctionalization (PCB) approach was designed for the construction of isomer-free fullerene bisadducts for efficient polymer solar cells. Abstract : Isomer-free fullerene bisadducts have been predicted to be high-performance acceptors for bulk-heterojunction (BHJ) solar cells. They can afford a higher open-circuit voltage compared with monoadducts because of the higher LUMO levels, and can also provide a higher short-circuit current and fill factor compared with the isomer mixture because of reduced energetic disorder. However, the application of isomer-free fullerene bisadducts in BHJ solar cells has met synthetic challenges. In this work, a new regioselective synthesis method, the so-called prebisaddition-confined bisfunctionalization (PCB), was developed for preparing isomer-free C60 bisadducts. This synthesis was highly selective for obtaining homo- and hetero-bisadducts with an " e configuration". Isomer-free C60 bisadducts, e -C60 [C(CO2 t Bu)2 ]2, e -NC60 BA and e -PPMF, were successfully synthesized via PCB. The gram-scale synthesis of e -C60 [C(CO2 t Bu)2 ]2 was realized. Single crystals of e -PPMF and two intermediates were obtained. Electrochemical studies proved that a single isomer has reduced energetic disorder. e -PPMF featuring a compact methano group and a solubilizing side chain showed good performance in P3HT and low-bandgap polymer solar cells. A decent power conversion efficiency (PCE) of 8.11% was achieved in solar cells consisting of e -PPMF and the low-bandgap polymer PPDT2FBT. The outstanding photovoltaic performance of e -PPMF among the fullerene bisadducts results from its better packing and reduced energetic disorder.